POTENTIAL ADDITION OF Lactobacillus casei AND FLOUR OF AMBON BANANA TO INHIBIT PATHOGENS AT YOGURT - Isti Handayani; Nur Aini (JITIPARI, 2021)
This study aims to determine the effect of Lactobacillus casei and Ambon banana flour on the viability of lactic acid bacteria and inhibition of pathogens in yogurt. The studies used the Randomized Block Design (RBD) 2 factor, starter type and ambon banana flour concentration. The starters type consisting of Streptococcus thermophillus and Lactobacillus bulgaricus; S. thermophilus, L. bulgaricus and L. casei.  The banana flour concentration consisting of 0; 2.5; 5.0; 7.5 and 10%. Analyzed used one-way ANOVA and continued with Duncan's Multiple Range Test. Variables observed including the viability of lactic acid bacteria, inhibition of pathogen (Escherichia coli and Staphylococcus aureus), and yogurt preference. The results showed that the addition of L. casei to yogurt cultures decreased the viability of lactic acid bacteria and inhibition of E. coli but increased inhibition of S. aureus. Increasing the concentration of banana flour causes increased viability of lactic acid bacteria, inhibiting against E. coli and S. aureus. The highest lactic acid bacteria viability has resulted in 10% banana flour concentration. Yogurt without the addition of banana flour cannot inhibit E. coli and S. aureus. Increasing the concentration of banana flour added to yogurt causes a decrease in preference.